Scoping Review: Overview of Gadget Use in Early Childhood COVID-19 Pandemic Period - Bee, Margareta Salsah; Pudjiati, Sri Redatin Retno (Psikostudia : Jurnal Psikologi, 2023)
The COVID-19 pandemic has caused significant changes in various aspects and habits of early childhood, including the use of gadgets. Changes in early childhood learning programs from face-to-face to online, school closures, to social activity restrictions have forced children to spend more time at home. This scoping review-based research was conducted to help describe how the use of gadgets in early childhood during the pandemic took place. There are 19 studies reviewed from the screening results of three online databases, namely Taylor & Francis, ScienceDirect, and Sage Journals. The results of the scoping review found that (1) there was a significant increase in the use of gadgets and screen time the early childhood; (2) parents are the main factor causing children to be exposed to gadgets; (3) excessive use of gadgets has impacts on developmental problems (e.g; fine motor, gross motor, lack of social interaction) and health problems (e.g; sleep disturbances) in early childhood.Pandemi COVID-19 telah menyebabkan perubahan signifikan dalam berbagai aspek dan kebiasaan anak-anak usia dini, termasuk dalam penggunaan gadget. Perubahan program pembelajaran anak usia dini dari tatap muka menjadi daring,  penutupan sekolah hingga pembatasan aktivitas sosial telah memaksa anak-anak untuk lebih banyak menghabiskan waktu di rumah. Scoping review ini bertujuan untuk  menggambarkan bagaimana penggunaan gadget pada anak usia dini selama masa pandemi berlangsung. Terdapat 19  studi yang dikaji dari hasil penyaringan tiga  basis data daring, yaitu Taylor & Francis, ScienceDirect, dan Sage Journals. Hasil scoping review menemukan (1) terjadi peningkatan signifikan pada penggunaan gadget dan paparan layar (screen time) pada anak usia dini; (2) orang tua merupakan faktor utama penyebab anak terpapar dengan gadget; (3) penggunaan gadget yang berlebihan pada anak berdampak pada masalah perkembangan (mis: motorik halus, motorik kasar, kurangnya interaksi sosial) dan masalah kesehatan (mis: gangguan tidur) pada anak usia dini.